1984
DOI: 10.2136/sssaj1984.03615995004800030022x
|View full text |Cite
|
Sign up to set email alerts
|

Ammonia Volatilization from Surface‐Applied Urea: Effect of Hydrogen Ion Buffering Capacity

Abstract: The influence of soil pH and soil cation exchange capacity on ammonia volatilization from surface applied ammoniacal nitrogen has been reported in previous studies. Since the hydrolysis of ureacontaining N fertilizers causes an increase in alkalinity, a soil's inherent H+ buffering capacity (defined as the soil's total acidity, comprised of exchangeable acidity plus non‐exchangeable, titratable acidity), should exert a dominant influence on the maximum soil pH at the site of urea fertilizer application. The ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
71
1
3

Year Published

1997
1997
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(83 citation statements)
references
References 0 publications
5
71
1
3
Order By: Relevance
“…In contrast to the effects of urea hydrolysis, ammonium sulfate and ammonium nitrate reduce NH 3 volatilization because they do not increase the pH of the soil surrounding the granule when they dissolve (Ferguson et al, 1984;Cantarella, 2007). Another factor that contributes to reduced ammonia losses from ammonium sulfate and ammonium nitrate is the presence of SO 4 2-and NO 3 -anions, which favor the migration of NH 4 + to regions with a lower pH and the retention of ammonia in soil colloids (Fenn & Hossner, 1985).…”
Section: Effects Of Urea Incorporation and Other N Sources On N-nh 3 mentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to the effects of urea hydrolysis, ammonium sulfate and ammonium nitrate reduce NH 3 volatilization because they do not increase the pH of the soil surrounding the granule when they dissolve (Ferguson et al, 1984;Cantarella, 2007). Another factor that contributes to reduced ammonia losses from ammonium sulfate and ammonium nitrate is the presence of SO 4 2-and NO 3 -anions, which favor the migration of NH 4 + to regions with a lower pH and the retention of ammonia in soil colloids (Fenn & Hossner, 1985).…”
Section: Effects Of Urea Incorporation and Other N Sources On N-nh 3 mentioning
confidence: 99%
“…Thus, N volatilization is favored by high urease activity in the surface layer of no-tilled soils (Barreto & Westerman, 1989) and the presence of straw on the soil surface, which limits contact between the soil and the fertilizer (Menguel, 1996). However, high soil moisture, organic matter content and CEC levels in the surface layer of NT soils are important factors increasing the buffer capacity of soil pH variation (Vieira et al, 2008) with possible effects decreasing NH 3 volatilization (Ferguson et al, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…Porém, o N apresenta uma dinâmica extremamente complexa no cultivo do arroz, com grande variabilidade nas suas formas químicas em função da umidade do solo (condições aeróbias ou anaeróbias), refletindo diretamente sobre a eficiência do aproveitamento do nutriente pela cultura (FILLERY et al, 1984).…”
Section: IIunclassified
“…They concluded that amount of ammonia-nitrogen in the water greatly influences the oviposition of these mosquitoes. It was reported earlier (Ferguson et al 1984, Rachhpal-Singh 1987 that surface-applied urea easily gets converted to unstable form, which quickly change to ammonia and carbon dioxide. Under less ideal conditions, the ammonia is lost to the atmosphere by volatilization.…”
mentioning
confidence: 99%